Battling COVID-19 and Disasters: Task Force Bureaucracy during Emergencies in the Philippines - S. Perez, Joe-Mar (Indonesian Association for Public Administration, 2025)
Coronavirus Disease 2019 (COVID-19) caused significant adjustments in the landscape of public governance in the Philippines. While the world was focused on the pandemic, the Philippines had to simultaneously address the impacts of disasters such as volcanic eruption and strong typhoons. In response, the government resorted to the use of